Enhancing the Effects of Power Sharing on Psychological Empowerment: The Roles of Management Control and Power Distance Orientation. (March 2014) - Chen, Chao C.; Zhang, Ann Yan; Wang, Hui
Abstract : In this article we test a model of bounded empowerment: the boundary conditions under which power sharing affects employees' psychological empowerment. Using data from two telecommunication companies, we investigate how management control and power distance orientation moderate the effects of supervisors' power sharing on employees' psychological empowerment. Results show that power sharing improves job performance partly through psychological empowerment. Furthermore, management control enhances rather than impedes the positive effect of power sharing on psychological empowerment. Power distance orientation further enhances management control's positive moderating effect on employee psychological empowerment. Limitations and implications for future research are also discussed.